ASSESSMENT RUBRIC FOR RESEARCH REPORT WRITING: A TOOL FOR SUPERVISION (Malaysian Journal of Learning and Instruction, 2021)
Purpose – Assessment rubric often lacks rigor and is underutilized. This article reports the effectiveness of the use of several assessment rubrics for a research writing course. Specifically, we examined students’ perceived changes and observed changes in their Chapter 1 thesis writing as assessed by supervisors using an existing departmental rubric and a new task-specific rubric.Methodology – Using action research methodology, two of the authors played active roles as the course supervisors, i.e., the practitioners. Two final year undergraduate students from a communication department (one from each supervisor) participated by writing three drafts of the first chapter of their research: (1) without a rubric, (2) with an existing departmental rubric, and (3) with a revised rubric. We collected artefacts of students’ writing drafts; students’ interviews; and supervisors’ reflections over the course of four months. We employed content analysis to evaluate students’ writing, while thematic analysis to analyze the students’ semi-structured interview and supervisors’ reflections.Findings – The findings suggest substantial improvements between the three drafts of students’ writing. Each student-supervisor pair acknowledged the improvements in the student’s writing after the introduction of the departmental rubric. With the newly revised rubric, they noted additional and more specific improvements especially in the scope of literature searches, problem statements, formulation of research questions, and operational definitions of variables; more generally, they also indicated improvements in the clarity of writing by using examples and providing relevant explanations tailored to the research topics.Significance – With effective scaffolding in supervision, students will regulate their learning and assess the quality of their own research report writing. We demonstrated the importance and benefits of a properly designed and validated rubric tailored to the program and course objectives to help students improve their writing drafts. Collective collaboration and input-sharing from faculty and instructors in developing and improving a rubric specific to the course and program objectives will produce quality assignments, provide constructive learning experiences for students, and achieve better grading for the program and department.